Pelatihan Pembuatan Pupuk Organik Cair (POC) dari Limbah Dapur untuk Menigkatkan Ketahanan Lingkungan Masyarakat Desa Mentoro - Fitri Umardiyah; Adiya Wahyu Pratama; Irkhamilatul Faizah; Trisna Putri Anggraeni; Muhammad Nasiruddin; Mucharommah Sartika Ami; Fatikhatun Nikmatus Sholihah (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2026)
Dependence on inorganic fertilizers remains a global problem often faced by farmers. Inorganic fertilizers provide quick results but have a negative impact on the environment if used in the long term. Therefore, environmentally friendly fertilization alternatives are needed, one of which is the use of liquid organic fertilizer (POC) derived from natural materials that can be processed independently by farmers. In Mentoro Village, most farmers and local communities still have minimal knowledge about the use and production of POC. The community service team held a socialization and training session for villagers on how to make POC from kitchen waste, namely shallot skins. The community service activity was held on August 20, 2025, at the Menturo Village Hall. The activity successfully increased participants' understanding of the use of household organic waste to produce liquid organic fertilizer (POC). Participants were able to practice making POC directly, from selecting materials, fermenting, to applying it to plants. The use of household organic waste to produce liquid organic fertilizer (POC) makes it easier for the community to obtain environmentally friendly fertilizer at a more affordable cost.